A Technical Review on Estimating Biomass of Fishes and Mammals: Non-Acoustic and Acoustic Approaches - Mallik, Avijit (International Journal of Integrated Engineering, 2020)
In marine ecosystem management, estimating biomass of marine species is the most significant challenge to control the ecology and biodiversity of a specified marine area and commercial fishery management. Many top-notch researches have been conducted for estimating the biomass of fishes and mammals. Most of the researches followed mainly two methods namely non-acoustics and acoustics techniques to estimate biomass. The non-acoustic technique is a very old terminology and many environmental conditions are to be considered as constant but in the acoustics method it is a much easier and error can be eliminated by different means of transforms. acoustic techniques can be classified in to two types, i.e., active acoustic techniques, and passive acoustic techniques. In this paper, we have reviewed the major acoustic and non-acoustic techniques for estimating biomass of fish and mammals. At the same time, performance analysis among these techniques has been discussed here. An introduction to the diversity in biomass estimation techniques of fishes and mammals is the aim of our investigation.